Systematization of the formative research process in the Medicine career - Ivan Ramon Gutiérrez Rojas; Hipólito Peralta Benítez; Adelaida Ballbé Valdés; Homero Calixto Fuentes González (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
The process of scientific research training in medical universities is generally discussed from a perspective focused especially on learning, delimited in the design of research and in the formulation of projects and to a lesser extent in its execution, as well as in the communication of the results of these. However, the developing role of high study centers demands the formation of investigative competencies based on the systematization of integrative knowledge of scientific research management. This article refers to a proposal for the systematization of the formative research process of professionals, a methodology contextualized by the authors for these purposes.